(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
This paper concentrates on the traditional naming practice connected with the creation of family names representing human physical defects. For many centuries, Ukrainians had been suffered from different anatomical defects, injuries, and irreversible defects that were not curable by surgery. Such anomalies regularly generated wide attention among members of society which led name-givers to use such special individual markers for the purposes of identification by creating new nicknames. First it was nicknames and then a lot of them developed into surnames. As a result, a substantial group of surnames that were derived from the words referring to some person’s flaws in the appearance was formed in the Ukrainian system of family names. Physical disabilities could serve as a source for name giving if they met several requirements: 1) they had external expression; 2) they were not very frequent; 3) they were easily seen on exposed parts of the body; 4) they were not curable by surgery. Brining the typology of medical diseases closer to the Ukrainian system of proper names it is possible to define some semantic groups of surnames: 1) surnames derived from the lexemes for the pathologies of the human eye; 2) surnames derived from the lexemes for the pathologies of the human ear; 3) surnames derived from the lexemes for the pathologies of the nose; 4) surnames derived from the lexemes for defects of the musculoskeletal system of a person; 5) surname derived from the lexemes for defects of the digestive system; 6) surnames derived from the lexemes for disorders of speech (disorders of the voice and form of speech); 7) surnames, reflecting the fact of injury or its consequences. It is also important to note that there are several subgroups within each group that accurately describe the physical lack. For example, surnames derived from the lexemes for the pathologies of the human ear include family names referring to the loss or decrease in hearing (deafness), some family names, which reflected the absence of ears, surnames that indicated the defects of the human ears. It is of remarkable importance to note the spoken nature of lexemes that were used in the name giving. Name givers preferred spoken words to depict medical concepts and didn’t use their Latin analogues for human physical defects.